Influence of culture conditions towards optimal carotenoid production by Gordonia alkanivorans strain 1B - Fernandes, Ana S. (2018)
ABSTRACT: With the increasing awareness on the toxicity of several synthetic dyes, demand for pigments from natural sources, such as microbial carotenoids, has gained interest as a promising safe alternative colour additive. In this study, a surface response methodology based on the Doehlert distribution for two factors [% of glucose in a mixture of glucose + fructose (10 g/L total sugars), and sulfate concentration] was used towards the optimal carotenoids production by Gordonia alkanivorans strain 1B in the presence of light (400 lx). Time influence on pigment production by this bacterium was also evaluated, as well as the cell viability profile during longer incubation periods at optimal conditions. Indeed, the highest carotenoid production (2596-3100 mu g/g(DCW)) was obtained when strain 1B was cultivated in the optimal conditions: glucose 10 g/L and sulfate >= 22 mg/L, in the presence of light for 19 days at 30 degrees C, 150 rpm. Flow cytometry showed that the highest production was somehow related with the cellular stress. These results highlight the great potential of strain 1B as a new hyperpigment producer to be exploited towards several applications.